Can the pharmaceutically active compounds released in agroecosystems be considered as emerging plant stressors? - Christou, Anastasis; Michael, Costas; Fatta-Kassinos, Despo; Fotopoulos, Vasileios (My University, 2018)
Pharmaceutically active compounds (PhACs) entering agroecosystems as a result of various human activities may be taken up by and accumulated within crop plants, with potential human health implications. Despite their extensive metabolism by a sophisticated enzyme-based detoxification system in plant cells, PhACs and their transformation products (TPs) may result in adverse effects on plants' physiology. PhACs–mediated phytotoxic effects, as well as plants' defense responses have been depicted on plants exposed to individual or low number of PhACs under controlled conditions. We highlight the need to consider the cocktails effects and synergistic interactions of PhACs present in mixtures in actual agroecosystems, towards phytotoxicity and agricultural sustainability in general. Considering PhACs as emerging plant stressors will better facilitate the understanding of their phytotoxic effects.
Keywords: Antibiotics; Cocktail effects; Oxidative stress; Phytotoxicity; Plant physiology; Reclaimed wastewater irrigation